Factors of individually-psychological and psychophysiological compatibility of sportswomen at selection to commands on group exercises of rhythmic gymnastics - Nesterova T.V; Kojanova O.S (Kharkov National Pedagogical University, 2010)
On the basis of the analysis of individually-psychological and psychophysiological characteristics of sportswomen the composition in group exercises of art gymnastics is formed. It is established that at divergences in a composition on the given indicators, solving should be a factor of individually-psychological compatibility of sportswomen. Basic value of a principle of compatibility at selection in commands on group exercises of art gymnastics is proved, according to which predisposition of the sportswoman to effective realization of individual multicomponent abilities in the conditions of command activity is established.